Comprehensive system limit state function model and its application for CRTS II track slab - Xuan-Yi Zhang; Zhao-Hui Lu; Yan-Gang Zhao; Chun-Qing Li (Journal of Asian Architecture and Building Engineering, 2022)
Considering safety and serviceability simultaneously, a comprehensive system limit state function (LSF) model and its application for CRTS II track slab is analyzed. First, a comprehensive system LSF model is proposed, and the procedure of comprehensive system reliability analysis is developed from integrating the method of moments with finite element (FE) code. Second, based on the proposed model, comprehensive system LSF of CRTS II track slab is constructed, considering five important safety failure modes and three important serviceability failure modes. Then, comprehensive system reliability of a CRTS II track slab on simply supported viaduct is analyzed using the proposed method, and the result is compared with general system reliabilities considering safety and serviceability separately. It is found that the proposed comprehensive system LSF model has a flexible form and the proposed methodology can be efficiently applied for comprehensive system reliability assessment. It is also found that comprehensive system reliability analysis is more appropriate compared with general system reliability analysis, and thus, comprehensive system reliability results can help to determine an appropriate maintenance strategy and ensure the safety operation for high-speed trains.